Seven Centuries of Unreal Wages The Unreliable Data, Sources and Methods that have been used for Measuring Standards of Living in the Past (Palgrave Studies in Economic History,, 2018)
The quality of life experienced by people in the past is one of the most important areas of historical enquiry, and the standard of living of populations is one of the leading measures of the economic performance of nations. Yet how accurate is the information on which these judgments are based? This collection of essays, written by renowned scholars in the fields of labour, wage and welfare history, cogently undermine the validity of the data that have for decades dominated the measurement of these phenomena in Britain, Europe and Asia, and provided the statistical backbone for countless descriptions and analyses of economic development, welfare and many other prime subjects in economic and social history. The contributors to this volume rigorously expose misapprehensions of long-run macroeconomic estimates of the real wage and provide a host of improved methods and data for revising and rejecting them. This volume is essential reading for anyone interested in economic and social history, economics and the application of statistical methods to historical evidence. John Hatcher is Emeritus Professor of Economic and Social History and Fellow of Corpus Christi College, University of Cambridge, UK. He is renowned for his wide ranging work on the economic, social and demographic history of England from the Middle Ages to the eighteenth century. He has also published a book about the experiences of the ordinary individuals who lived and died in the Black Death, which combines history with fiction. Judy Stephenson is a postdoctoral fellow in Economic History at Wadham College, University of Oxford, UK. She researches and publishes work on early modern employment, work and labour markets. She published her first book Contracts and Pay: Work in London Construction 1660-1785 with Palgrave Macmillan in 2018.